TIM-3 Regulates Distinct Functions in Macrophages - Ocaña-Guzman, Ranferi; Torre-Bouscoulet, Luis; Sada-Ovalle, Isabel (Frontiers in Immunology, 2016)
The transmembrane protein TIM-3 is a type I protein expressed by sub-types of lymphoid cells, such as lymphocytes Th1, Th17, Tc1, Nk, as well as in myeloid cells. Scientific evidence indicates that this molecule acts as a negative regulator of T lymphocyte activation, and that its expression is modified in viral infections or autoimmune diseases. In addition to evidence from lymphoid cells, the function of TIM-3 has been investigated in myeloid cells, such as monocytes, macrophages and dendritic cells (DC), where studies have demonstrated that it can regulate cytokine production, cell activation and the capture of apoptotic bodies. Despite these advances, the function of TIM-3 in myeloid cells and the molecular mechanisms that this protein regulates are not yet fully understood. This review examines the most recent evidence concerning the function of TIM-3 when expressed in myeloid cells, primarily macrophages, and the potential impact of that function on the field of basic immunology